GPR-Driven Geomechanical Modeling and Drill-Blast Optimization for Enhanced Efficiency in Open-Pit Gold Mining - Almenov, Talgat; Zhanakova, Raissa; Shautenov, Mels; Askarova, Guljan; Agybayev, Nurdaulet; Assylkhanova , Samal (Civil Engineering Journal, 2025)
This study seeks to raise the operational efficiency and economic return of the Vasilkovskoye open-pit gold mine by integrating real-time ground-penetrating-radar (GPR) monitoring, geomechanical modeling, and digital optimization of drilling-and-blasting parameters. Continuous GPR scanning identified hazardous fracture zones that were subsequently characterized in DIPS and RS2 to model slope stability, while ShotPlus-based blast simulations and OrePro 3D displacement modeling guided the redesign of hole spacing, charge distribution, and delay timing. Fragmentation quality was verified with high-resolution photogrammetry and correlated to blast design through statistical analysis; a comparative techno-economic assessment quantified cost and dilution differentials between conventional and optimized schemes. The integrated workflow established a robust predictive link between blast geometry and fragment size, reducing oversize generation by 17% and ore dilution by 9%, while increasing gold grade in mill feed from 0.84 g t⁻¹ to 0.94 g t⁻¹. GPR-informed hazard mapping eliminated unplanned wall failures, and the revised pattern lowered specific explosive consumption without compromising fragmentation, cutting total unit costs by 8%. Unlike previous studies that treat slope stability and blasting as separate tasks, this study couples deformation dynamics with blast design in a single digital loop, offering a transferable framework for automation-ready, risk-aware mine planning at complex geological sites.